2023
DOI: 10.3389/fcvm.2023.1070450
|View full text |Cite
|
Sign up to set email alerts
|

Phasic left atrial strain to predict worsening of diastolic function: Results from the prospective Berlin Female Risk Evaluation follow-up trial

Abstract: PurposeThe predictive value of maximum left atrial volume index (LAVI), phasic left atrial strain (LAS) and other standard echocardiographic parameters assessing left ventricular (LV) diastolic function to discriminate a future worsening of diastolic function (DD) in patients at risk is unclear. We aimed to prospectively assess and compare the clinical impact of these parameters in a randomly selected study sample of the general urban female population.Methods and resultsA comprehensive clinical and echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
(67 reference statements)
2
8
0
Order By: Relevance
“…Indeterminate diastolic function was present in 85 and overt DD in 8 study patients. As reported in the preceding manuscript, 16 women with DD were older, had higher BMI and NTproBNP values and a higher prevalence of arterial hypertension, diabetes mellitus type 2, and coronary heart disease. Besides that, they had more increased LV wall thickness, increased LAVI, a longer isovolumetric relaxation time (IVRT) and transmitral E wave deceleration time (DecT), higher E/e’ values, a lower LV GLS, and lower LA reservoir strain.…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…Indeterminate diastolic function was present in 85 and overt DD in 8 study patients. As reported in the preceding manuscript, 16 women with DD were older, had higher BMI and NTproBNP values and a higher prevalence of arterial hypertension, diabetes mellitus type 2, and coronary heart disease. Besides that, they had more increased LV wall thickness, increased LAVI, a longer isovolumetric relaxation time (IVRT) and transmitral E wave deceleration time (DecT), higher E/e’ values, a lower LV GLS, and lower LA reservoir strain.…”
Section: Resultssupporting
confidence: 64%
“…Previous studies exploring the relationship between diastolic dysfunction and myocardial deformation measured by strain (the precursor and integral component of myocardial work) have established a close association between the two 16,18 and showed that phasic left atrial strain entails predictive value in evolving diastolic dysfunction 16 . Furthermore, in their study, Brand et al.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations